Cementum protein 1 transfection does not lead to ultrastructural changes in nucleolar organization of human gingival fibroblasts. (27th April 2018) - Villegas‐Mercado, C. E.; Agredano‐Moreno, L. T.; Bermúdez, M.; Segura‐Valdez, M. L.; Arzate, H.; Del Toro‐Rangel, E. F.; Jiménez‐García, L. F.
Abstract : Background and Objective: Transfection of cementum protein 1 (CEMP1) into human gingival fibroblasts (HGFs) notably increases cell metabolism and results in overexpression of molecules related to biomineralization at transcriptional and protein levels. Therefore, HGF‐CEMP1 cells are considered as putative cementoblasts. This represents a significant advance in periodontal research because cementum neoformation is a key event in periodontal regeneration. In addition, it is well known that important changes in cell metabolism and protein expression are related to nucleolar structure and the function of this organelle, which is implicated in ribosome biogenesis. The aim of this study was to determine the effect of transfecting CEMP1 gene in human HGF on the ultrastructure of the nucleolus. Material and Methods: Cells were processed using the conventional technique for transmission electron microscopy, fixed with glutaraldehyde, postfixed with osmium tetraoxide, and embedded in epoxy resin. Semi‐thin sections were stained with Toluidine blue and observed by light microscopy. Thin sections were stained with uranyl acetate and lead citrate. For ribonucleoprotein detection, the staining method based on the regressive effect of EDTA was used. In addition, the osmium ammine technique was used for specific staining of DNA. Results: The results obtained in this study suggest that transfection of CEMP1 into HGFs does not produce changes in the general nucleolar ultrastructure because the different components of the organelle are present as fibrillary centers, and dense fibrillar and granular components compared with the control. Conclusion: The transfection of CEMP1 into HGFs allows these cells to perform cementoblast‐like functions without alteration of the ultrastructure of the nucleolus, evaluated by the presence of the different compartments of this organelle involved in ribosomal biogenesis.